Performance improvement of a portable electric generator using an optimized bio-fuel ratio in a single cylinder two-stroke engine - Misron, Norhisam (MDPI, 2011)
The performance of an electrical generator using bio-fuel and gasoline blends of different composition as fuel in a single cylinder engine is presented. The effect of an optimized blend ratio of bio-fuel with gasoline on engine performance improvement and thereby on the electrical generator output is studied. Bio-fuels such as ethanol, butanol and methanol are blended with gasoline in different proportions and evaluated for performance. The effects of different bio-fuel/gasoline blending ratios are compared experimentally with that of the gasoline alone using the output power developed by the electric generator as the evaluation parameter. With a composition of 10% ethanol–gasoline, the engine performance is increased up to 6% and with a blending ratio of 20% butanol–gasoline the performance is increased up to 8% compared to the use of 100% gasoline. The investigations are performed on a portable generator used in palm tree harvesting applications.